The Impact of Negative Investment List (NIL) Introduction on Investment Decisions of Foreign and Domestic Investors in Indonesia: - - Wildatul Fitri Tatiara; Toshihiro Kudo (Pusbindiklatren Bappenas, 2021)
As an investment intervention policy, NIL is present to grant legal certainty to investors and invite more investment. Its existence has possible impacts on investment decisions. However, the studies of its effect are limited, focusing only on specific NIL versions and sectors. To fill this gap, the present paper investigates the impact of NIL introduction on the investment decisions of foreign and domestic investors in Indonesia by utilizing all NIL versions and business field-level data of the planned investment values from 2005 to 2018. The analysis shows, first, the NIL introduction may generate the investment inflows from both FDI and DDI. Second, there was a parallel movement of crowding-in effect between foreign and national firms responding to the investment opportunities open to both parties. This study suggests that more detailed and transparent information should be provided in the NIL to guarantee its effectiveness.